Evaluation of vitamin D level, iron homeostasis, and hematological parameters following two weeks of live-high-train-high altitude in elite female and male alpine skiers - Haghbin, M.; Tahmasebi, W.; Azizi, M.; Hoseini, R. (Science & Sports, 2024)
Background The association of vitamin D and hematological factors and their changes during high altitude training remains unclear among alpine skiers. This study aimed to evaluate the vitamin D level, iron Homeostasis, and hematological parameters in alpine skiers following two weeks of ski training at high altitude.